The use of a bacterin vaccine in broiler breeders in the control of Ornithobacterium rhinotracheale in commercial broilers - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2003.